2010
DOI: 10.1038/ng0110-16
|View full text |Cite
|
Sign up to set email alerts
|

Getting connected in the globin interactome

Abstract: n e w s a n d v i e w s candidate genes (AGER, TNS1, HTR4, THSD4 and GSTCD) were shown to be expressed in lung tissue 2 . These loci are all biologically plausible candidates that are involved in pathways known to be important in lung biology, including immune function, muscle function or inflammation. These studies did not replicate the SERPINE2 association and also did not find evidence for association to the 15q CHRNA5-CHRNA3-CHRNB4 locus previously associated with nicotine dependence, lung cancer and COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…5) can be sufficient to allow the formation of widespread gene interactions while preserving CTs as higher-order chromatin structures. As a growing body of evidence supports the formation of cell type specific ‘interactomes’ during cell differentiation [18][23], it is important to understand how different patterns of gene expression correlate with the formation of interaction networks and how these interactions define spatial and temporal changes in genome structure and function within individual cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) can be sufficient to allow the formation of widespread gene interactions while preserving CTs as higher-order chromatin structures. As a growing body of evidence supports the formation of cell type specific ‘interactomes’ during cell differentiation [18][23], it is important to understand how different patterns of gene expression correlate with the formation of interaction networks and how these interactions define spatial and temporal changes in genome structure and function within individual cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, validation of specific inter-chromosomal interactions within individual cells typically demonstrated that only ∼10% of the loci in question were co-associated when transcribed [19], [21], [22]. Nevertheless, recent innovations in analysis of genome-wide interaction networks or functional ‘interactomes’, have placed unprecedented emphasis on understanding how chromatin dynamics facilitate the formation of gene interactions networks, which in turn might contribute to the regulation of gene expression in mammalian cells [18], [23].…”
Section: Introductionmentioning
confidence: 99%